Association between Statin Use and Sensorineural Hearing Loss in Type 2 Diabetic Patients: A Hospital-Based Study - Hye-Won Han; Jeong Yee; Yoon-Hee Park; Hye-Sun Gwak (Pharmaceuticals, 2021)
Statins have emerged as protective agents against sensorineural hearing loss (SNHL) associated with dyslipidemia, but the effects of statins on SNHL are not consistent. The purpose of this study was to investigate the association between statin use and the risk of SNHL using a hospital cohort. This nested case-control study included type 2 diabetic patients over the age of 18 years without a history of hearing loss. Of these, 1379 patients newly diagnosed with SNHL or tinnitus were classified as cases, and 5512 patients matched to the cases based on age, sex, and index year were classified as controls. Chi-squared tests were used to compare categorical variables between the two groups. Odds ratios (ORs) and adjusted odds ratios (AOR) were calculated from univariate and multivariable unconditional logistic regression analyses, respectively. There was a significant difference in the prevalence of statin use between the cases and controls (53.7% vs. 61.2%, respectively; p < 0.001). The use of statins in type 2 diabetic patients significantly reduced the risk of SNHL or tinnitus by 24.8% (95% CI 14.2–34.1%, p < 0.001) after controlling for confounders. Similar results were found for the association between statin use and SNHL (AOR = 0.706; 95% CI 0.616–0.811, p < 0.001). The protective effects of statins against SNHL were consistent regardless of age and sex. The use of statins for type 2 diabetic patients was significantly associated with a reduced risk of SNHL, regardless of age and sex. Further studies are needed, especially large cohort studies, to evaluate the long-term protective effects of statins.